PELATIHAN PEMBUKUAN APLIKASI BUKUKAS BAGI PELAKU USAHA DI DESA KUTAMUKTI - Alda Miranda; Vita Aprilina; Yuha Nadhirah Qintharah (Komunitas Dosen Indonesia, 2022)
This Community Service activity aims to make Micro, Small and Medium Enterprises (MSMEs) in Kutamukti Village able to understand and prepare financial reports using the Bukukas application, for MSME actors and their calculations after participating in this activity. Many incidents show that MSME actors in Kutamukti Village experience obstacles in understanding and compiling financial reports in the Bukukas Application, for MSME actors and their calculations. Among the contributing factors are the educational background of MSME actors who still do not support the required competencies, and also the lack of training for MSME actors related to the business they are running. Micro, small and medium enterprises (MSMEs) have quite serious problems, namely poor fund management in carrying out their business activities. At this time there are still many business actors who in running their businesses do not use information technology applications, they still use books to record their finances. One solution to this problem is to do good bookkeeping using an android-based financial bookkeeping application. Android-based financial accounting applications are the solution to these problems. The purpose of this study was to compare the Android-based MSME financial bookkeeping application based on the criteria for a quality accounting application. The data analysis technique used is by observation, interviews. The methods or procedures used during the training are lectures, discussions, and community questions and answers. The training in this activity was attended by 5 participants giving scores by filling out the pre-test and post-test with the aim of determining the effectiveness of the activity. The results of the activity show that this training has been running quite effectively and participants can understand the application of bookkeeping through the application.